Towards deep reading learning: Language teachers’ practices in employing reflective thinking skills among primary school students - Al-Barakat, Ali Ahmad; Bataineh, Ruba Fahmi; AlAli, Rommel Mahmoud; Al-Hassan , Omayya; Bataineh, Rula Fahmi; Abdullatif, Ali Khalifa; Aboud, Yusra Zaki; Zaher, Ashraf (Research Journal in Advanced Humanities, 2026)
This study investigates the practices of language teachers in employing reflective thinking skills to promote deep reading learning among primary school students. A quantitative descriptive approach was adopted, and data were collected through a structured classroom observation checklist designed to document teachers’ actual instructional practices during reading lessons. The observation tool was developed based on an extensive review of the literature on reflective thinking and reading pedagogy, and it comprised five key domains representing reflective practices in reading instruction: Visual Perception Skills (VPS), Identifying Fallacies Skills (IFS), Drawing Conclusions Skills (DCS), Providing Convincing Explanations Skills (CES), and Proposing Solutions Skills (PSS). The checklist was reviewed by experts to ensure content validity, and its reliability was verified through pilot testing prior to the main data collection. The study sample consisted of 60 primary language teachers from schools in Amman, Jordan, selected using a convenience sampling method. Each teacher was observed twice during reading lessons, resulting in a total of 120 classroom observations. Descriptive statistics and a three-way ANOVA were employed to analyze the data and examine whether teachers’ practices differed according to teaching experience, gender, and academic qualification. The results indicated that language teachers demonstrated a high level of performance in employing reflective thinking skills across all five domains. Teachers consistently encouraged students to analyze textual details, identify inconsistencies, draw conclusions, justify interpretations, and propose possible solutions, reflecting a strong emphasis on reflective and analytical engagement with reading materials. The findings also revealed no statistically significant differences in teachers’ practices attributable to teaching experience, gender, or academic qualification. Overall, the study provides empirical evidence of the integration of reflective thinking practices within primary reading instruction. The findings highlight the importance of classroom practices in fostering deeper comprehension and critical engagement with texts, and they offer practical insights that may inform teacher professional development programs and curriculum design aimed at strengthening deep reading learning in primary education.